188k views
2 votes
What is the solution to the following equation?2(3x + 5) - 2x + 2 = 0

User Underverse
by
5.8k points

1 Answer

4 votes

The initial equation is:

2(3x + 5) - 2x + 2 = 0

By distributive property:

2(3x) + 2(5) - 2x + 2 = 0

6x + 10 - 2x + 2 = 0

Then, we sum the terms with an x and the terms without an x, as:

(6x - 2x) + (10 + 2) = 0

4x + 12 = 0

Subtracting 2 on both sides:

4x + 12 - 12 = - 12

4x = - 12

Dividing by 4 on both sides of the equation:


\begin{gathered} (4x)/(4)=(-12)/(4) \\ x=-3 \end{gathered}

Answer: x = -3

User Jim Bolla
by
6.2k points